2020
DOI: 10.1101/2020.06.01.127951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BARD1 links histone H2A Lysine-15 ubiquitination to initiation of BRCA1-dependent homologous recombination

Abstract: Protein ubiquitination at sites of DNA double-strand breaks (DSBs) by RNF168 recruits BRCA1 and 53BP1, mediators of the homologous recombination (HR) and non-homologous 20 end joining (NHEJ) DSB repair pathways, respectively. While NHEJ relies on 53BP1 binding to ubiquitinated Lysine 15 on H2A-type histones (H2AK15ub), an RNF168-dependent modification, the mechanism linking RNF168 to BRCA1 recruitment during HR has remained unclear. Here, we identify a tandem BRCT domain ubiquitin-dependent recruitment motif (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…BARD1, also bearing two BRCT domains at its C-terminus, has been shown to be critical for the mobilization of the heterodimer to DNA damaged sites by recognizing PAR molecules at DNA lesions, regardless of the H2AX status ( 98 ). Recently, it has been reported that BARD1 was able to bind ubiquitylated H2A at lysine 15 directly through its BUDR (BRCT domain ubiquitin-dependent recruitment) motif and this occurred synergistically with the binding of its ankyrin repeat domain (ARD) to H4K20me0, generating a strong interaction between damaged chromatin and BARD1 in S and G2 phases ( 87 ).…”
Section: Brca1: Safeguard Of the Genomementioning
confidence: 99%
“…BARD1, also bearing two BRCT domains at its C-terminus, has been shown to be critical for the mobilization of the heterodimer to DNA damaged sites by recognizing PAR molecules at DNA lesions, regardless of the H2AX status ( 98 ). Recently, it has been reported that BARD1 was able to bind ubiquitylated H2A at lysine 15 directly through its BUDR (BRCT domain ubiquitin-dependent recruitment) motif and this occurred synergistically with the binding of its ankyrin repeat domain (ARD) to H4K20me0, generating a strong interaction between damaged chromatin and BARD1 in S and G2 phases ( 87 ).…”
Section: Brca1: Safeguard Of the Genomementioning
confidence: 99%
“…Very recently, BARD1 has also been suggested to recognize H2AK15ub in human cells [83], highlighting a possible Ub reader-writer crosstalk between N-and C-terminal H2A Ub marks, which should be further explored and characterized.…”
Section: Readers and Consequences Of H2a Ubiquitination At K13/15mentioning
confidence: 99%
“…A recent study revealed that BARD1 localizes to DNA damage sites through a dual mechanism involving both the ANK and BRCT domains 26 . The BARD1 ANK domain is a reader of histone H4 unmethylated at K20 (H4K20me0) 17 , and the BRCT repeat was shown to contain a BRCT domain ubiquitin-dependent recruitment motif (BUDR), which directly binds mUb-H2A 26 . Indeed, MCF7 BARD1 -/cells engineered to express a BARD1 BUDR mutant construct (Fig.…”
Section: S3d)mentioning
confidence: 99%
“…In the current study, we report an RNF168-governed pathway that is responsible for the recruitment of the BRCA1-P complex to DSBs. A BUDR was recently discovered within the BARD1 BRCT domain, which directly binds mUb-H2A 26 . In support of this, mutating residues within the BUDR, or specifically blocking the ability of RNF168 to generate mUb-H2A, reduced BRCA1-P complex recruitment to DSBs.…”
Section: S3d)mentioning
confidence: 99%
See 1 more Smart Citation